Anxiety, depression, social phobia, and quality of life in Turkish patients with acne and their relationships with the severity of acne - ÖZTÜRK, AHMET; Ozturk, AHMET; DEVECİ, ERDEM; Deveci, ERDEM; Bagcioglu, Erman; ATALAY, Figen; SERDAR, Zehra (My University, 2013)
Aim: To investigate the psychiatric characteristics of acne vulgaris and the effects of the disease on quality of life.
Keywords: Anxiety